Rediscovery of Terebratulina austroamericana Zezina, 1981 (Brachiopoda: Cancellothyrididae) from off northern Chile - Araya, Juan Francisco; Bitner, Maria Aleksandra (Zootaxa, 2018)
Phylum Brachiopoda, shelled marine invertebrates, is currently represented by about 400 extant species; a tiny fraction of the ca. 30,000 described fossil species (Emig et al. 2013; Bitner 2014; Nauendorf et al. 2014; Logan et al. 2015). Only twenty of these Recent species are known from the Chilean coasts (Lee et al. 2008), most of them from subtidal waters. Of these, only Magellania venosa (Dixon, 1789) (the largest extant brachiopod) and Discinisca lamellosa (Broderip, 1833) are common species found in the southern and central-northern coasts of the country, respectively. As with other marine invertebrates, brachiopods from the region have been reviewed in few studies, apart from some classic nineteenth century works by Sowerby (1822); Broderip (1833); Davidson (1878, 1888); Dall (1895, 1902, 1908), and by Dall and Pilsbry (1891). More recent studies include Cooper (1973, 1982) and Foster (1989) reviewing brachiopods from the Southern Hemisphere and the extreme South Pacific; Zezina (1981, 1989) describing species from the underwater ridges of the Eastern Pacific; Moyano (1995) who revised all the literature dealing with Brachiopoda in Chile; and most recently Baumgarten et al. (2014) who studied the population structure of Magellania venosa in the fjord region of southern Chile.